1997
DOI: 10.1038/37635
|View full text |Cite
|
Sign up to set email alerts
|

Reduced fertility and postischaemic brain injury in mice deficient in cytosolic phospholipase A2

Abstract: Phospholipase A2 (PLA2) enzymes are critical regulators of prostaglandin and leukotriene synthesis and can directly modify the composition of cellular membranes. PLA2 enzymes release fatty acids and lysophospholipids, including the precursor of platelet-activating factor, PAF, from phospholipids. Free fatty acids, eicosanoids, lysophospholipids and PAF are potent regulators of inflammation, reproduction and neurotoxicity. The physiological roles of the various forms of PLA2 are not well defined. The cytosolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
657
3
8

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 817 publications
(693 citation statements)
references
References 24 publications
25
657
3
8
Order By: Relevance
“…[15][16][17][18] Mice with the genes for PLA2G4A and PLA2G2A nullified (knocked out) do not produce eicosanoids, have reduced incorporation rates of free AA into cell membranes, yet normal AA levels. 19,20 PLA2G6A cleavage of phospholipids is primarily for the purpose of cellular membrane remodelling, by altering phospholipids/fatty acid ratios and modifying membrane fluidity. 21,22 Loss of PLA2G6A function leads to significant reductions in the amount of AA incorporated into the cell membrane.…”
Section: Pla2s and Aamentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18] Mice with the genes for PLA2G4A and PLA2G2A nullified (knocked out) do not produce eicosanoids, have reduced incorporation rates of free AA into cell membranes, yet normal AA levels. 19,20 PLA2G6A cleavage of phospholipids is primarily for the purpose of cellular membrane remodelling, by altering phospholipids/fatty acid ratios and modifying membrane fluidity. 21,22 Loss of PLA2G6A function leads to significant reductions in the amount of AA incorporated into the cell membrane.…”
Section: Pla2s and Aamentioning
confidence: 99%
“…22,[39][40][41] While not required within apoptotic neurons, complete loss of PLA2G4A and PLA2G2A abolishes inflammation following central nervous system (CNS) injury, and reduces neuronal apoptosis. 19 Studies have shown how PLA2G4A is expressed in adjacent glial cells postinjury, but not within apoptotic neurons. 42,43 Together this indicates a primary role for PLA2G6A activity in neuronal remodelling by apoptosis, while PLA2G4A and PLA2G2A act peripherally to manage inflammation.…”
Section: Memory Formation (Long-term Potentiation)mentioning
confidence: 99%
“…Interestingly, macrophages from mice deficient in cPLA 2 -α produced no prostaglandins or leukotrienes and various disease models have now been studied in these animals [5]. These mice demonstrate reduced fertility and reduced brain injury after cerebral ischaemia [6][7][8]. Three human paralogs of the cPLA 2 -α enzyme have also been identified, termed cPLA 2 -β, cPLA 2 -γ and cPLA 2 -δ [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The primary means by which AA is released from membranes is the agonist induced activation of the calcium dependent group IV  isoform of cPLA 2 , due to its high specificity and selectivity for glycerophospholipids containing AA at the sn-2 position. Although the agonist induced activation of cPLA 2  has been established as the rate limiting step of eicosanoid biosynthesis (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), the deacylation of diacylglycerol (DAG) via DAG lipase also produces AA for the synthesis of eicosianoids. In addition, DAG lipase has been suggested to mediate the release of AA in KCs (56,62).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of cPLA 2 in eicosanoid production is further evident as cells and tissues from cPLA 2 -deficient mice fail to produce prostaglandins, leukotrienes, and thromboxanes (20,21). It is established that the primary function of cPLA 2  is to mediate agonist-induced release of AA for eicosanoid production (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The regulation of cPLA 2 activity involves multiple components.…”
Section: Introductionmentioning
confidence: 99%